2014
DOI: 10.1177/0145445514543466
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Physical Environment in Promoting Physical Activity in Children Across Different Group Compositions

Abstract: Physical activity is an important health-related behavior, but the environmental variables that promote or abate it are not well understood. The purpose of this study was to conduct a functional analysis evaluating the effect of the physical environment on moderate-to-vigorous physical activity (MVPA) in preschool children, and to evaluate the utility of the methodology across different group compositions. The Observational System for Recording Physical Activity in Children was used to define the test conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…In a subsequent study, Larson, Normand, Morley, and Miller () conducted a brief intervention analysis to determine whether MVPA would occur at the same level observed in the FA if the relevant condition was used as an intervention. The results of Larson et al () were consistent with those of Larson et al () in that the highest level of MVPA occurred in the interactive play condition, followed by the attention condition, for all participants.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…In a subsequent study, Larson, Normand, Morley, and Miller () conducted a brief intervention analysis to determine whether MVPA would occur at the same level observed in the FA if the relevant condition was used as an intervention. The results of Larson et al () were consistent with those of Larson et al () in that the highest level of MVPA occurred in the interactive play condition, followed by the attention condition, for all participants.…”
supporting
confidence: 78%
“…There is growing evidence that the social environment can influence activity levels (e.g., Larson, Normand, Morley, & Hustyi, ; Larson, Normand, Morley, & Miller, ; Larson, Normand, Morley, & Miller, ; McKenzie, Crespo, Baquero, & Elder, ; Morrissey, Wenthe, Letuchy, Levy, & Janz, ; cf. Hastmann, Foster, Rosenkranz, Rosenkranz, & Dzewaltowski, 2012), suggesting that well‐established strategies for developing function‐based interventions might be applied to the problem of physical inactivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were several methodological concerns amongst the included studies. The main concerns were: sample size not being described in detail (only eight studies Systematic review of nature play and child health described their sample [73][74][75][76][77][78][79][80]; the lack of sample size justification (only three studies did this [73,74,81]; lack of reliability and validity of outcome measures [ten studies reported on reliability [73-76, 78, 79, 81-84] and seven reported on validity [73-76, 81, 82, 84]; and finally the lack of reporting dropouts, with only six studies reporting dropout rates [5,74,75,81,83,84].…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…The authors found that the fixed‐activity condition produced the most moderate‐to‐vigorous physical activity (MVPA) for all participants, and that this type of assessment could be used to identify the effects of different antecedent manipulations on the physical activity of children. Larson, Normand, Morley, and Hustyi () found that a fixed‐activity condition combined with the presence of a peer produced the most MVPA for all participants, and that different environmental compositions resulted in differential responding observed across conditions. Larson, Normand, Morley, and Miller (, ) extended this line of work by conducting a functional analysis of MVPA with typically developing preschool children.…”
mentioning
confidence: 99%